Energy Storage: Polyanion‐Type Electrode Materials for Sodium‐Ion Batteries (Adv. Sci. 3/2017) - Ni, Qiao (Adv Sci (Weinh), 2017)
Na‐ion batteries, promising large‐scale energy storage and conversion devices, can store wind and solar energy through smart grids efficiently, that provides power supply to thousands of households. In article number 1600275, Chuan Wu and co‐workers systematically summarize the characteristics of different kinds of polyanion‐type compounds for Na‐ion batteries. In addition, constructive strategies to enhance the electrochemical performances of such materials are also proposed. [Image: see text]